Assessment of the Influence of Dust-Salt Aerosols of the Aral Sea on the Morphological Characteristics of the Tissue of the Epididymis of Rats in the Experiment - Suleimen, A.; Rakhimova, B.; Jangildinova, S.; Aitkulov, A.; Yessilbayeva, B.; Dyussenbekova, B; Danilenko, M.; Beygam, N. (OnLine Journal of Biological Sciences, 2024)
Drying of the Aral Sea is a very significant environmental problem of modern times. Dust particles from the dried seabed are spread over long distances and negatively impact the quality of life of residents in nearby areas. One of the significant problems is the decrease in the fertility of residents of the Aral region, but there is insufficient data about the influence of dust-salt aerosols on the functioning of the reproductive organs of men. We assessed the influence of dust particles from the dried bed of the Aral Sea on the microstructure and some morphometric parameters (tubule diameter and height of epithelium) of the epididymis of rats. In this experimental study, 21 white rats (males) were divided into the following three groups: The first experimental group with a duration of inhalation exposure of seven days and the second experimental group with inhalation of seventy-two days. Inhalation exposure for the white laboratory male rats was conducted for 4 h daily for both experimental groups. For administration purposes, a fine aerosol composed of particles from the dried part of the Aral Sea was employed. The animals were exposed to a toxic dose of sodium chloride (the main component in the aerosol) amounting to 1.5 mg/m³. After the completion of the inhalation exposure, the experimental animals were fixed, epididymides were removed and stained. The microstructure of stained epididymis preparations of the rats from the control and experimental groups was examined in comparison. In the experimental groups, after inhalational exposure to dust-salt aerosols from the Aral Sea, interstitial edema and deterioration in the hemodynamics of the epididymis, destructive changes in the lumen of the tubules, decrease in the height of the epididymal epithelium, a reduction in the number and uneven distribution of spermatozoa in the tubules were observed. Short-term and long-term exposure to dust particles from the dried part of the Aral Sea can cause reproductive dysfunction due to damage to the tissues of the epididymis and disruption of sperm maturation.
Keywords: Dust-Salt Aerosols; Aral Sea; Inhalation Exposure; Rat; Epididymis